Hamadiana chapadensis, a new genus and species of diving beetle from Brazil (Coleoptera, Dytiscidae, Laccophilinae, Laccophilini) - Benetti, Cesar J.; Short, Andrew E. Z.; Michat, Mariano C. (Zootaxa, 2019)
Hamadiana chapadensis gen. n. and sp. n. is described based on a single male specimen collected in Central Brazil. The new species belongs to the diving beetle tribe Laccophilini but could not be assigned to any existing genera, therefore a new genus is described to accommodate it. Hamadiana gen. n. is unique among Laccophilini in having the hind margin of the metacoxal process deeply incised and medially slightly protruded backwards. In addition, it differs from other genera of the tribe by having the antennomeres simple, not expanded, the metacoxal lines not straight, and the metatibiae with two simple apical spurs. The habitus, male genitalia, and diagnostic features are illustrated, and a distribution map is provided. A recently published key to Laccophilini is modified to include the new genus.